1999
DOI: 10.1136/jcp.52.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of keratins 10, 17, and 19 in normal cervical epithelium, cervical intraepithelial neoplasia, and cervical carcinoma

Abstract: Aim-To examine the value of immunohistochemistry in defining a keratin profile to aid cervical histopathological diagnosis. Methods-Immunohistochemical localisation of keratins 17, 10, and 19 was studied in 268 cervical biopsies from 216 women including normal epithelia (with and without human papilloma virus), low and high grade cervical intraepithelial neoplasia, and invasive carcinoma. The percentage of positive immunostaining was scored using a Kontron MOP videoplan image analyser. Results-All major catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 12 publications
6
28
0
1
Order By: Relevance
“…Moreover, Noguchi et al [19] reported that CK17 immunoexpression and mRNA expression increased as the grade of epithelial dysplasia advanced. Similar results were reported in the uterine cervix [23,27,28], oesophagus [24] and larynx [29], underscoring the potential utility of CK17 as a marker for malignancy in squamous cells.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, Noguchi et al [19] reported that CK17 immunoexpression and mRNA expression increased as the grade of epithelial dysplasia advanced. Similar results were reported in the uterine cervix [23,27,28], oesophagus [24] and larynx [29], underscoring the potential utility of CK17 as a marker for malignancy in squamous cells.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, the mean value of CK 17 mRNA over-expression is signiWcantly stronger in patients with T1 and T2 OSCC and at early stages, compared to that of CK 19 and CK 20. With agreement to other studies (Carrilho et al 2004;Smedts et al 1992;Maddox et al 1999;Martens et al 1999), it might be suggested that over-expression of CK 17 mRNA is speciWc to tumor cells of OSCC in a high percentage, and that early stages of squamous cell carcinoma might be associated with the presence of CK 17. Thus determination of CK 17 mRNA over-expression could contribute to distinguish ND not detected a Value of CK mRNA RQ was deWned as positive if the value was higher more than 2.5 and as negative if less than 2.5, as described in the Materials and methods section b The statistical signiWcance of the association was determined by the chi-square test c The clinical stages were determined according to the International Union Against Cancer (UICC) d The histological diVerentiation grades were determined according to the WHO (Chu et al 2005;Goldstein and Bassi 2001).…”
Section: Discussionsupporting
confidence: 62%
“…Our results show that these keratins are highly expressed in tumoral tissue compared to non-tumoral surgical margins. Other studies have shown the presence of K17 in gastric adenocarcinoma, Ewing sarcoma, OSCC, and ovary, breast, and cervical cancers (Maddox et al, 1999;Ide et al, 2012;Kitamura et al, 2012;Alshareeda et al, 2013;Sankar et al, 2013;Wang et al, 2013). K19 expression was shown in liver, breast, lung, ovary, thyroid and oral cancers (Safadi et al, 2010;Isic Dencic et al, 2013;Kong et al, 2013;Liu et al, 2013;Park et al, 2013).…”
Section: Discussionmentioning
confidence: 89%